T-cell lymphoblastic lymphoma of the uterus complicated by Chlamydia trachomatis pneumonia. Issue 723 (January 1986) - Cunningham, D.; Gilchrist, N. L.; Lee, F. D.; Haxton, M.; Heppleston, A.; Forrest, G. J.; Soukop, M.
Abstract : This is the first documented case of a T-cell lymphoblastic lymphoma arising in the uterus. At presentation, the patient also had a life-threatening pneumonia due to Chlamydia trachomatis which responded to erythromycin and tetracycline. Cytotoxic therapy produced partial tumour regression, but the patient died 14 weeks after diagnosis, probably as a result of intercurrent infection.